Neodzivnost na peroralno antiagregacijsko zdravljenje - Perme, Rok (Zdravniški vestnik, 2006)
Background Antiplatelet treatment with aspirin and/or clopidogrel reduces the incidence of atherothrombotic events but does not abolish them altogether. ln a multifactorial pathological process such as atherothrombosis no single preventive strategy cart be completely successful, yet prescribing antiplatelet treatment without routinely measuring its efficacy raises concern. Results Several studies using different methods have shown that a substantial part of the population is non-responsive or semi-responsive to oral antiplatelet treatment. These people have a higher incidence of atherothrombotic events, such as myocardial infarction, ischemic stroke, worsening of limb ischemia or cardiovascular death. The main problem in assessing non-responsiveness to antiplatelet treatment is that laboratory methods in vitro can only roughly estimate the function of platelets in vivo. Currently, there is no consensus reither on standardized testing of platelet function or on clinical decisions based on testing but several clinical studies are addressing these issues. Conclusions Current clinical guidelines do not eecommend routine platelet function testing in patients on antiplateletmedication, but these guidelines may be revised in the future based on results of ongoing clinical studies.
Keywords: antiagregacijsko zdravljenje; Aspirin; Cerebrovascular Disorders; Cerebrovaskularne motnje; drug; Drug Resistance; neodzivnost; Platelet Aggregation Inhibitors; Platelet Function Tests; therapy; Trombociti, funkcijski testi; Trombociti, zlepljenje, inhibitorji; učinkovanje; zdravila; Zdravilo, rezistenca; zdravljenje